Tahrif in the Scripture: A Study of Ahmad Khan's Tabyin al-Kalam - Yusuf Rahman (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 1999)
The present paper is a study of Tabyin al-Kalām, especially in relation to the notion of taḥrīf. Some scholars, like Bruce B. Lawrence, believe that Ahmad Khar’s thought was not original, and depended heavily on al-Tafsīr al-Kabir of Fakhr al-Dīn al-Rāzī (d. 1209). In order to assess this assumption, the paper will also compare Tabyin al-Kalām with al-Tafsīr al-Kabir.